Shoot the Message, Not the Messenger—Combating Pathogenic Virulence in Plants by Inhibiting Quorum Sensing Mediated Signaling Molecules - Alagarasan, Ganesh; Aswathy, Kumar S.; Madhaiyan, Munusamy (Frontiers in Plant Science, 2017)
Immunity, virulence, biofilm formation, and survival in the host environment are regulated by the versatile nature of density dependent microbial cell signaling, also called quorum sensing (QS). The QS molecules can associate with host plant tissues and, at times, cause a change in its gene expression at the downstream level through inter-kingdom cross talking. Progress in controlling QS through fungicide/bactericide in pathogenic microscopic organisms has lead to a rise of antibiotic resistance pathogens. Here, we review the application of selective quorum quenching (QQ) endophytes to control phytopathogens that are shared by most, if not all, terrestrial plant species as well as aquatic plants. Allowing the plants to posses endophytic colonies through biotization will be an additional and a sustainable encompassing methodology resulting in attenuated virulence rather than killing the pathogens. Furthermore, the introduced endophytes could serve as a potential biofertilizer and bioprotection agent, which in turn increases the PAMP- triggered immunity and hormonal systemic acquired resistance (SAR) in plants through SA-JA-ET signaling systems. This paper discusses major challenges imposed by QS and QQ application in biotechnology.